2019
DOI: 10.1002/celc.201900756
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall MoS3 Loaded GO Nanocomposites as High‐Rate and Long‐Cycle‐Life Anode Materials for Lithium‐ and Sodium‐Ion Batteries

Abstract: MoS3 is a promising anode material due to its high theoretical capacity (838 mAh g−1), high conductivity, low cost, and environmental friendliness. However, the big volume changes upon cycling can induce particle pulverization, leading to a poor cycling performance, especially at high rates. Herein, nanocomposites of amorphous ultrasmall MoS3 nanoparticles and loaded graphene oxide (GO/MoS3) have been prepared via a facile acid precipitation method. Three nanocomposites were obtained by changing the amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Though, to the best of our knowledge, controllable preparation of 2D amorphous MoS 3 ‐based heterostructure has not yet been reported. [ 48,49 ]…”
Section: Introductionmentioning
confidence: 99%
“…Though, to the best of our knowledge, controllable preparation of 2D amorphous MoS 3 ‐based heterostructure has not yet been reported. [ 48,49 ]…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, the wide discharge plateau exhibited less than 0.7 V, suggest battery chemistry could be controlled by either parasitic reaction resulting in the formation of metallic molybdenum (MoS 2 + 4Li → 2Li 2 S + Mo) or intercalation of lithium ion in the RGO nanostructure . Zhou et al demonstrated the application of MoS 3 -loaded graphene oxide composite electrode, with a capacity of ∼400 mA h/g at a current load of 500 mA h/g, for lithium-ion batteries . Also, alleviating the passivation layer formed by irreversible Li 2 S is also crucial toward long-life Li–S battery.…”
Section: Introductionmentioning
confidence: 99%
“…At 2 Ag −1 The reversible capacity is 334.6 mAhg −1 after 1200 cycles at high current density. Zhou et al 103 prepared nanocomposites of amorphous ultra‐small MoS 3 nanoparticles and supported graphene oxide (GO/MoS 3 ). The sodium storage property was optimized by changing the amount of GO in the composite.…”
Section: Anode Materialsmentioning
confidence: 99%